Wolbachia Pipientis as a Natural Biocontrol Agent to Inhibit Dengue Virus Replication in Aedes Aegypti Mosquitoes - A Aida Ariya; Rahmawati Rahmawati; Yusminah Hala (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Wolbachia pipientis is an endosymbiotic bacterium commonly found in insects, arthropods, and certain nematodes, playing a pivotal role in host reproductive manipulation and pathogen resistance enhancement. This review aims to provide a comprehensive understanding of the characteristics, physiology, and ecological roles of Wolbachia pipientis, as well as its potential in vector control strategies to combat insect-borne diseases. A literature-based approach was employed, utilizing peer-reviewed scientific journals from reputable sources such as Scopus and Web of Science. The analysis revealed that Wolbachia pipientis is a Gram-negative bacterium with a small size (0.2 to 0.5 µm) that reproduces through binary fission within host cells and relies on the host for essential nutrients. It modulates host gene expression and enhances host immunity, thereby reducing the transmission of pathogens like dengue, Zika, and chikungunya through cytoplasmic incompatibility. Furthermore, Wolbachia pipientis has shown potential in managing filariasis by inhibiting nematode reproduction. The bacterium's ability to alter host reproductive dynamics through mechanisms like feminization and parthenogenesis makes it an effective tool in biocontrol programs. The findings underscore the importance of Wolbachia pipientis in improving public health and environmental sustainability by controlling disease vectors and supporting ecological balance. This review highlights the need for further research to explore genetic engineering approaches to enhance the effectiveness of Wolbachia pipientis in global health management.